After Europe - Krastev, Ivan (University of Pennsylvania Press, 2017)
In this provocative book, renowned public intellectual Ivan Krastev reflects on the future of the European Union--and its potential lack of a future. With far-right nationalist parties on the rise across the continent and the United Kingdom planning for Brexit, the European Union is in disarray and plagued by doubts as never before. Krastev includes chapters devoted to Europe's major problems (especially the political destabilization sparked by the more than 1.3 million migrants from the Middle East, North Africa, and South Asia), the spread of right-wing populism (taking into account the election of Donald Trump in the United States), and the thorny issues facing member states on the eastern flank of the EU (including the threat posed by Vladimir Putin's Russia). He concludes by reflecting on the ominous political, economic, and geopolitical future that would await the continent if the Union itself begins to disintegrate.